ChemInform Abstract: Organocatalytic Asymmetric Michael Addition of 1, 3‐Cyclohexanedione to Benzylidenemalonitriles. Issue 20 (20th May 2014) - Suh, Chang Won; Kim, Dae Young
Abstract A facile synthesis of chiral 2‐amino‐4H‐chromene derivatives with excellent enantioselectivity (up to 99% e.e.) via a binaphthyl‐modified squaramide‐catalyzed Michael addition of cyclohexanedione to benzylidenemalonitriles is developed.